Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1365-2818.1997.2180777.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the section thickness and optical disector height with a simple calibration method

Abstract: The distance between the upper and lower surfaces of a section (i.e. the section thickness) can be measured with a microcator or a shaft encoder. In the present report, an alternative simple method is described for estimating the section thickness where such equipment is not available. The basic principle of the method is based on a calibration method already described in the literature. The main difference is that it enables one to make more precise measurements. Provided that the calibration and measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The development of multiple animal epilepsy models and investigation on surgical tissue from epileptic patients have showed the morphological changes in the epileptogenic brain (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of multiple animal epilepsy models and investigation on surgical tissue from epileptic patients have showed the morphological changes in the epileptogenic brain (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of each of the sections used in the analysis was measured at seven or eight points that were randomly selected from the area of the DG, i.e., as previously described by Korkmaz and Ttimkaya (15). The mean thickness of the section was calculated for each of the section used in the analysis.…”
Section: Operationmentioning
confidence: 99%
“…In his argument, however, there are essential points with respect to our method (Korkmaz & Tü mkaya, 1997) that might be misleading either for the audience likely to read our article or for the potential users of this method and that should be supplemented by some additional information. As mentioned in our article (Korkmaz & Tü mkaya, 1997), differential focusing is considered to be the most precise and simple technique for estimating the section thickness, but has its own requirements that should be taken into consideration when it is applied (Uylings et al, 1986;West et al, 1991). These detailed studies have shown that one can be assured that the resulting estimates of the section thickness are unbiased when the prepared sections are thick enough (i.e.…”
Section: Replymentioning
confidence: 97%
“…Estimation of the section thickness and optical disector height with a simple calibration method SIR, I have read the article by Korkmaz & Tü mkaya (1997). They cover very well the problem of obtaining a thickness value for coverslips using a careful measurement of the difference between well-focused images of the top and bottom surfaces of the coverslip as read from calibrated microscope fine adjustment positions.…”
mentioning
confidence: 99%
“…At each step in the sampled pyramidal cell layer, the distance between the top and the bottom surfaces i.e., the positions at which the neuronal nuclei first came into focus from above and below the section, was determined (Korkmaz and Tümkaya, 1997), indicating that shrinkage is homogeneous within each studied section. The mean thickness of each section was calculated.…”
Section: Section Thicknessmentioning
confidence: 99%